Collective Imaginaries in Deconstruction. Perspectives from the voices of Villaleyvan women (Boyacá) - Pérez Bermúdez, Hingrid Camila; Mosquera Ferro, Tatiana Fernanda; Pérez Bermúdez, Hingrid Camila; Mosquera Ferro, Tatiana Fernanda; Pérez Bermúdez, Hingrid Camila; Mosquera Ferro, Tatiana Fernanda (Corporación Universitaria Americana, 2020)
The collective imagery is part of the social media that mobilizes acts, practices, thoughts, feelings and fallacies that inhabit the conscious and unconscious of human beings. Therefore, through this article and from the research titled "Public policy of gender equality for women in the municipality of Villa de Leyva-Boyacá", the beliefs of "certain" realities imposed by the patriarchal structure. From the participatory action as an implemented methodology, imaginary such as: economic contributions, decisions at home, valuation of activities and intersectional violence, are reconstructed from the voices of Villaleyvan women.